2020
DOI: 10.1021/acs.jmedchem.9b01478
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Balovaptan, a Vasopressin 1a Receptor Antagonist for the Treatment of Autism Spectrum Disorder

Abstract: We recently reported the discovery of a potent, selective, and brainpenetrant V1a receptor antagonist, which was not suitable for full development. Nevertheless, this compound was found to improve surrogates of social behavior in adults with autism spectrum disorder in an exploratory proof-of-mechanism study. Here we describe scaffold hopping that gave rise to triazolobenzodiazepines with improved pharmacokinetic properties. The key to balancing potency and selectivity while minimizing P-gp mediated efflux was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…26 Further, the triazolobenzodiazepine, balovaptan (RG7314) showed encouraging results for the treatment of ASD in a clinical phase II study, which led to a Breakthrough Therapy Designation by the U.S. FDA in January 2018. 27 Despite these encouraging preclinical findings, the potential of V1A antagonists for the treatment of cardiovascular and immune-mediated diseases is largely unexplored. This has, at least in part, been attributed to the lack of appropriate tools for in vivo imaging of V1A receptors in peripheral organs.…”
Section: Introductionmentioning
confidence: 99%
“…26 Further, the triazolobenzodiazepine, balovaptan (RG7314) showed encouraging results for the treatment of ASD in a clinical phase II study, which led to a Breakthrough Therapy Designation by the U.S. FDA in January 2018. 27 Despite these encouraging preclinical findings, the potential of V1A antagonists for the treatment of cardiovascular and immune-mediated diseases is largely unexplored. This has, at least in part, been attributed to the lack of appropriate tools for in vivo imaging of V1A receptors in peripheral organs.…”
Section: Introductionmentioning
confidence: 99%
“…Vasopressin (AVP) and oxytocin have been implicated in the etiology of psychiatric disorders, such as schizophrenia [1], autism [2][3][4], and depression [5]. AVP acts centrally within the central nervous system (CNS) where it modulates a range of behaviors from learning and memory and responses to stressors to social behaviors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study by Ferris et al [10] suggested that V 1A receptor antagonists may be used to treat interpersonal violence co-occurring with an illness such as attention-deficit/hyperactivity disorder, autism, bipolar disorder, and substance abuse. Therefore, it is hypothesized that antagonistic action on the V 1A receptor might attribute to the treatment approach in anxiety-like behavior and recently, discovery of a potent, selective, and brain penetrant V 1A receptor antagonist is emerging [4,11]. Additionally, AVP had been reported to mediate brain edema formation and cerebral ischemia by regulating water permeability in astrocytes [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intranasal OXT has been found to improve social behaviour deficits in autistic adolescents-a promising result (LeClerc & Easley, 2015;Parker et al, 2017). The pharmacological investigation into the role of the vasopressin 1a receptor (V1a) in the improvement of social-communicative abilities found that its inhibition improved social deficits and social living skills (Bolognani et al, 2019;Schnider et al, 2020). Balovaptan, an orally administered V1a receptor antagonist is currently undergoing phase 3 clinical trials for the treatment of adults (ClinicalTrials.gov, 2020a) and phase 2 for the treatment of children (ClinicalTrials.gov, 2020b).…”
Section: Treatmentmentioning
confidence: 99%